Towards the Development of a Monolingual Sesotho Learner’s Dictionary - Mahloane, Malefu Justina (University of the Witwatersrand, Johannesburg, 2023)
Sesotho practical lexicography commenced over 160 years ago and up to the time when this research was initiated, there had not been a single monolingual or online learner’s dictionary produced for the language. As a result, this research aimed to develop a Sesotho monolingual learner’s dictionary with the ultimate goal being to make the dictionary available online. To achieve this, the research investigated the different factors to consider when developing a dictionary with these characteristics. The objective of this research was to use Corpus Linguistics methodology to develop the dictionary. The methods used are both qualitative and quantitative. The contents of the dictionary are extracted from a c.a. 100 000-word corpus that was compiled specially for this research – as a corpus is the object of study or a tool in Corpus Linguistics. The corpus was processed using various language processing methods and tools, the main being the TshwaneLex Suite. The study managed to develop a prototype of the Sesotho monolingual learner’s dictionary and it is attached as Annexure 1, and the dictionary will continue to be developed beyond this research. It is anticipated that, the developed prototype dictionary presented here, will serve as evidence that there are effective means that Sesotho Lexicographers can adapt to produce other types of dictionaries beyond the usual bilingual/translation and paperback dictionaries that are the norm in Sesotho lexicography.
A Masters dissertation submitted in fulfilment of the requirements for the degree of Master of Arts in African Languages & Linguistics, in the Faculty of Humanities, School of Literature, Language and Media, to the University of the Witwatersrand, Johannesburg, 2023.
Keywords: Corpus Linguistics; Corpus building; Sesotho Lexicography; African Languages Lexicography; TshwaneLex; Monolingual Dictionary; Dictionary-making tools; Learner’s dictionaries; UCTD; SDG-4: Quality education